Atitude pró-ambiental e desperdício de alimentos: um estudo com a Geração Z sob o efeito moderador do gênero - Magna Lourdes Lisboa Dietrich (2024)
Brazil loses approximately 30% of the food it produces every year. The UN's Agenda 2030, which aims to guide the world towards a more sustainable path, warns of the problems caused by waste and sets the goal of halving both losses and global food waste. This dissertation deals with this issue, with the aim of analyzing the correlation between general and pro-environmental attitudes towards food waste among Generation Z individuals. Generation Z is more concerned about the environment and more willing to incorporate sustainable practices into their lifestyle. To this end, the Theory of Planned Behavior (TPB) was used as a theoretical foundation. In the case of this dissertation, the work is applied and descriptive. Data was collected online using a structured questionnaire with answers on a Likert scale, which made it possible to verify the relationship between different attitudes and intentions not to waste food. The data was analyzed using a multiple regression technique. The main findings confirm that general attitudes and pro-environmental attitudes have a positive impact on the intention not to waste food in generation Z, highlighting gender differences and revealing the moderating role of gender in this relationship.